2009
DOI: 10.1111/j.1948-7134.2009.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Hantaan virus at Twin Bridges Training Area, Gyeonggi Province, Republic of Korea, 2005-2007

Abstract: The Twin Bridges Training Area (TBTA) in the Republic of Korea consists of dirt roads, barren training areas, and forested hillsides adjacent to linear and broad expanses of tall grasses, herbaceous, and scrub vegetation. Of the six species of small mammals, the striped field mouse, Apodemus agrarius, was the most frequently captured (96.1%). Apodemus agrarius capture rates varied from 17.7 to 33.2% during three trapping periods. Gravid females were observed during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
(15 reference statements)
2
20
0
Order By: Relevance
“…We found that HTNV Ab + rates were positively correlated with weight (age) of A. agrarius. This is similar to other studies and is highly suggestive that the primary source of infection is horizontal, resulting from wounding or indirect transmission from HTNV in the environment, rather than vertical (transplacental or during nesting) (Glass et al 1988, Douglas et al 2001, Sauvage et al 2002, Hinson et al2004, Kallio et al 2006, Sames et al 2009T.A.K., unpublished data). During the spring (March-April, 4.2%-40%) and the fall (August-September, 24.5%-70%) periods at various training sites, there were significant increases in the proportions of gravid females (O'Guinn et al 2008;T.A.K., unpublished data).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We found that HTNV Ab + rates were positively correlated with weight (age) of A. agrarius. This is similar to other studies and is highly suggestive that the primary source of infection is horizontal, resulting from wounding or indirect transmission from HTNV in the environment, rather than vertical (transplacental or during nesting) (Glass et al 1988, Douglas et al 2001, Sauvage et al 2002, Hinson et al2004, Kallio et al 2006, Sames et al 2009T.A.K., unpublished data). During the spring (March-April, 4.2%-40%) and the fall (August-September, 24.5%-70%) periods at various training sites, there were significant increases in the proportions of gravid females (O'Guinn et al 2008;T.A.K., unpublished data).…”
Section: Discussionsupporting
confidence: 84%
“…To support this, HFRS cases among ROK populations are not correlated with the seasonal prevalence of HTNV Ab + in A. agrarius . While HTNV Ab + rates tend to be higher for disturbed or space-limited habitats than for larger areas, capture rates are generally lower (Sames et al 2009, Kim et al 2011. When these factors are taken into consideration for transmission potential, relatively undisturbed habitats had similar or higher densities of HTNV Ab + mice based on capture rates (T.A.K., unpublished data).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations